PEMBINGKAIAN TAJUK RENCANA TENTANG MUSIBAH JATUHNYA CRANE DAN TRAGEDI TEROWONGAN MINA ARAB SAUDI 2015 - Siswanta, Aris Wibowo, Maya Sekarwangi & (Transformasi, 2016)
This riset aims to determine the process of framing the Editorial in Kompas and MediaIndonesia regarding preaching crane collapse disaster and tragedy in Mina Tunnel SaudiArabia during September 2015. Various media reported events occurred including MediaIndonesia and Kompas that have a critical view of the events by presenting in the form ofeditorial section. Both were chosen for presenting editorial appearing more and editorialsections crane collapse disaster in the Haram and tragedy in the tunnel Mina interesting tostudy the news amid other disasters shown by Indonesian media. Elements of communicationare examined in this study is the message that communicate newspaper Kompas and MediaIndonesia as a communicator to a broad audience as receive through the print media.Departing from the concept of sense extension theory thinking related to agenda setting is doneby the news media in conveying information. In the process of conveying information newspapermedia constructs reality and the result is the editorial text. Text editorial examined using dataanalysis Pan and Kosicki framing models. Framing analysis model is a model derived from theanalysis of discourse. This type of research used in this research is descriptive qualitative. Theobject of research that is used for data or an information in the study were related to Editorial /Editorial in Kompas and Media Indonesia in the news regarding the Fall Accidents News Craneand Mina Tunnel tragedy in Saudi Arabia during September 2015. The data collection techniqueusing the documentation and study of literature , And data analysis techniques using frameworkanalysis model framing Zhongdan Pan and Gerald M. Kosicki. So the results of this study arethe Media Indonesia over the frame into themes: the government's stance Countries of originpilgrims who are victims. While the focus Compass by framing dish emotional audience ofreaders in response to the incident.Keywords: framing analysis, Pan and Kosicki, tragedy in haji 2015, Media Indonesia andKompas